PULMONARY METASTASES FROM FIBROSARCOMA: A CASE REPORT - Amiruddin; Pasca Sari Nauli Tamba; Lely Hartati (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
Introduction: Pulmonary metastases arising from extremity fibrosarcoma are among the most common sites of distant metastasis. The median survival after the occurrence of metastasis is approximately one year. Patients treated with nonoperative therapy have a median survival of 11 months. Case Illustrations: A 70-year-old female, never smoker, admitted to the hospital with a chief complaint of shortness of breath. The patient had a history of fibrosarcoma on the left foot followed by surgery a year ago. Chest X-ray showed central lung mass with massive right pleural effusion. Post-contrast chest imaging revealed a heterogeneous, enhancing, lobulated mass in both lungs. TTNA and core biopsy were performed under USG guidance on the lung mass. The cytologic findings revealed a metastatic neoplasm-suggestive sarcoma. The concomitant core biopsy showed a histologic pattern of spindle cells arranged in short intersecting fascicles suggestive of metastases of fibrosarcoma. The patient showed rapid deterioration resulting in death on the 20th day of hospitalization. Discussion: The incidence of fibrosarcoma in the lower limb accounts for 40% of all cases of soft tissue tumors. Patient with extremity sarcomas are more likely to have distant metastases as their initial site of recurrence. From the histologic pattern, those patients with spindle cell sarcoma were the most likely to have pulmonary metastases. Data on pulmonary metastases arising from extremity fibrosarcoma is poorly available making it difficult to treat metastatic sarcoma. Conclusion: Pulmonary metastases from fibrosarcoma are a challenging issue, with a median survival of less than one year post-metastasis. Pulmonary metastasectomy can extend survival to 33 months, but a multidisciplinary approach, including tailored chemotherapy and radiotherapy, is crucial due to the diverse tumor behaviors. This case highlights the rapid progression and poor prognosis of metastatic fibrosarcoma, underscoring the need for comprehensive treatment strategies.